A review on methods used to reduce drag of the ship hulls to improve hydrodynamic characteristics. Issue 4 (21st December 2020) - Kumar, Susheel; Verma, Kumari Ambe; Pandey, Krishna Murari; Sharma, Kaushal Kumar
The most severe component is the frictional resistance in hydrodynamic design of the vessel. Pressure resistance can be decreased by modifying the shape of the vessel with integration of modern and more sophisticated hull forms. Since hull form optimisation is not cost effective method and sometimes impossible for decreasing drag in existing ships. Ships use large quantities of fuel to provide the necessary propulsive power and to overcome resistance in their motion across ocean surfaces. In this paper the various techniques used in the maritime industry to reduce the resistance on the hull of a ship along with their advantages and disadvantages have been discussed. On the basis of results from various reviewed research the combination of hull form optimisation method and air lubrication through injection and antifouling coating is highly recommended to decrease the total resistance on the vessel.